2015
DOI: 10.1159/000435949
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Primary Resistance of <b><i>Helicobacter pylori</i></b> to Clarithromycin and Levofloxacin in Southern Spain

Abstract: Background: The eradication of Helicobacter pylori (HP) using clarithromycin (CLA)-based triple therapy depends on the resistance of HP to antibiotics. The Maastricht III conference recommends the implementation of locoregional surveillance programmes for primary resistance of HP to CLA. In Andalusia, there are no previous data in this respect. The aim of this study was to determine the prevalence of the primary resistance of HP to CLA and levofloxacin (LF) in southern Spain. Methods: Multicentre cross section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 18 publications
9
17
0
Order By: Relevance
“…Similar results were also reported in Belgium, where multiple mutations were found in 25% of samples for fluoroquinolones and 12% for clarithromycin[19]. Finally, simultaneous resistance to both antibiotics was unusual (4.3%) in our study, similar to what was reported in South Africa (2.5%)[22], Hong Kong (3.7%)[36], Italy (1.6%)[37], and Spain (4%)[38]. …”
Section: Discussionsupporting
confidence: 89%
“…Similar results were also reported in Belgium, where multiple mutations were found in 25% of samples for fluoroquinolones and 12% for clarithromycin[19]. Finally, simultaneous resistance to both antibiotics was unusual (4.3%) in our study, similar to what was reported in South Africa (2.5%)[22], Hong Kong (3.7%)[36], Italy (1.6%)[37], and Spain (4%)[38]. …”
Section: Discussionsupporting
confidence: 89%
“…18 Our LV-R isolates showed the mutation D91N and N87K in 84.6%. 3,25,26 No resistance to amoxicillin or tetracycline was observed, in line with the very low resistance rates described by other authors. These results emphasized the importance of phenotypic antimicrobial susceptibility testing prior treatment since molecular techniques available only detect the most frequent mutations associated with resistance.…”
Section: Discussionsupporting
confidence: 88%
“…[24][25][26] The main cause of fluoroquinolone resistance is mutation in the QRDR at position 87 and 91. Primary LV-R was 13.1%, much lower than the 38.7% recently reported in the northwest of Spain, 3 but in line with other Spanish studies.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial resistances to H. pylori , however, are increasing worldwide and hinder the success of such empirical treatments. The work by Narravo-Jarabo et al [2] , published in the last issue of Digestion, shows that in the Spanish region of Andalusia, primary resistances to clarithromycin and levofloxacin may vary considerably from individual to individual. Their multicenter study revealed that primary resistance to the key antibiotic -clarithromycin -was ranging from 11 to 25%, primary resistance to levofloxacin was ranging from 7 to 17%.…”
mentioning
confidence: 99%
“…Continuous surveillance studies that monitor the present state of antimicrobial resistance are indispensable to establish updated guidelines on first-line eradication treatments. Remarkably, Narravo-Jarabo et al [2] tested the resistance to clarithromycin and levofloxacin at the molecular genetic level by identification of mutations conferring resistance. International guidelines recommend susceptibility testing after a second failure of empirical treatments [1].…”
mentioning
confidence: 99%